An Analysis and Research on Ways to Enhance the Identification of Traditional Chinese Culture in the Context of Cross-Cultural Communication - Jiang, Hongwei (Journal of Theory and Practice of Social Science, 2024)
Any nation can only establish cultural self-confidence and national self-confidence by scrupulously abiding by its own cultural identity. A nation without cultural identity and cultural self-confidence is difficult to survive and develop in the increasingly fierce international competition. Cultivating and establishing cultural identity and cultural self-confidence is the cornerstone of a nation's development and progress. At present, we are facing a crisis of Chinese traditional cultural identity. In the current cross-cultural communication context, it is our urgent task to speed up the establishment of the Chinese traditional cultural identity. There are two ways to enhance the Chinese traditional cultural identity. Most of the epidemics from the 19th century to the 20th century were caused by the health environment, such as plague, cholera, and smallpox. To this end, Macau promulgated a series of environmental improvement systems, such as the "Urban Improvement Report" in 1883, the "Epidemic Prevention Regulations" and the "Epidemic Prevention Regulations" in 1894, and the later improved "New Epidemic Prevention Regulations". A series of measures to improve the sanitation environment, such as streets, rebuilding old houses, building new toilets, cleaning houses, cleaning sewers and planting plants to improve climate and air. In addition, in response to the characteristics of different epidemics, corresponding environmental control measures have been made, such as installing rodent-proof siphons at sewers during the plague outbreak.